2018
DOI: 10.19111/bulletinofmre.495321
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Assessment of Radiation Exposure Risks of Farmers’ in Odo Oba, Southwestern Nigeria

Abstract: The toxicity risks of being over exposed to ionizing radiation in the environments are of great concern to environmental and health scientists. The distribution of radioactivity concentrations of thorium, uranium and potassium were studied in randomly selected soil samples from ten (10) farm locations in Odo Oba, southwestern Nigeria in order to determine the radiological risks of farmers' exposure to radionuclides. The mean estimation of thorium and potassium are greater than the global average by factors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The levels of 238 U, 232 Th , their respective progenies and the non-series 40 K have been studied in different building materials (both raw and finished products) from different parts of the country [[6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22]], but none has been carried out in Kwara State despite the increasing level of granite mining and usage in this part of the country. Also, data from University of Ilorin Teaching Hospital (UITH) shows that 74 different cancers of 2246 (891 male and 1355 female) cancer patients within the age of 1–105 were recorded at the University of Ilorin Teaching Hospital (UITH) cancer registry between the period of 2007 and 2016 [23].…”
Section: Methods Detailsmentioning
confidence: 99%
“…The levels of 238 U, 232 Th , their respective progenies and the non-series 40 K have been studied in different building materials (both raw and finished products) from different parts of the country [[6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22]], but none has been carried out in Kwara State despite the increasing level of granite mining and usage in this part of the country. Also, data from University of Ilorin Teaching Hospital (UITH) shows that 74 different cancers of 2246 (891 male and 1355 female) cancer patients within the age of 1–105 were recorded at the University of Ilorin Teaching Hospital (UITH) cancer registry between the period of 2007 and 2016 [23].…”
Section: Methods Detailsmentioning
confidence: 99%
“…The Basement Complex and Sedimentary rocks are the major rocks that are believed to have covered Nigeria almost in equal proportions. The rocks of Basement Complex are considered to be PreCambrian in age [[7], [8], [9], [10]], while the sediments varied from Upper Cretaceous to Recent in age [6,[11], [12], [13]]. The Basement Complex rocks are composed of igneous and undifferentiated metamorphic rocks, as well as their weathering products (which are popularly known as overburden).…”
Section: Methods Detailsmentioning
confidence: 99%
“…Generally, granites are enriched in 238 U and 232 Th [28]. The ratio of 232 Th to 238 U could be high in some fractured or fault zones in Basement Complex terrain [10,29,30], while it could be low in some terrain where uranium has not undergone depletion due to lack of fluid infiltration [31], as revealed in the case of [20].
Fig.
…”
Section: Methods Detailsmentioning
confidence: 99%
“…Environmental researchers have been concerned about the overexposure from ionizing radiation in agricultural practice for a long time. Adagunodo et al (2019) explored the distribution of radioactive thorium, potassium, and uranium in soil samples selected from 10 farms located in Odo Oba, Nigeria, to measure the exposure risks of farmers to radioactive elements. The authors found that the studied sites contained much higher potassium and thorium concentration than the global average, while uranium concentration is lower than the global one.…”
Section: Safety Assessmentmentioning
confidence: 99%